FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP INDEKS HARGA SAHAM GABUNGAN PADA BURSA EFEK INDONESIA - Yohandes Rabiqy (universitas teuku umar, 2017)
Abstract: The purpose of this study was to determine the effect of the inflation, IBCinterest rate, and exchange rate on CSPI. The research was conducted on the Indonesia Stock Exchange (ISE) by using sample of 72 consisted of the entire variable monthly data during 2010 to 2015 with the selection of the sample through a non probability sampling method by purposive sampling method and the data were analyzed with multiple linear regression analysis techniques. Based on the analysis found inflation, IBC interest rates, and exchange rates simultaneously affect the CSPI. The Inflation and IBC interest rates partially significant negative effect on the CSPI, this means an increase in inflation and IBC interest rates may result decrease value of CSPI. Exchange rates partially significant positive effect on CSPI. This means that the increase occurred in exchange rates can increase the value of CSPI.Kata kunci: Inflasi, Suku Bunga, Kurs, Indeks Harga Saham Gabungan (IHSG)